Highly flexible deep-ultraviolet photodetectors using amorphous gallium oxide thin films grown by atomic layer deposition - Lee, Kang Min; Kim, Se Eun; Kim, Sun Kyung; Lee, Sang Woon (Materials Today Communications, 2022)
Flexible deep ultraviolet (DUV) photodetectors have increased applicability in healthcare and electronic skin, however, sufficient flexibility of DUV photodetectors has not yet been achieved. In this study, we developed highly flexible DUV photodetectors using amorphous gallium oxide (GaOx) films grown by atomic layer deposition, which enabled a bending radius as small as 1.5 mm. The high flexibility originated from a residual compressive strain in the GaOx films and the amorphous nature of the thin GaOx films (~ 25 nm) grown on polyimide substrates. Therefore, the high flexibility of DUV photodetectors can provide a promising opportunity in healthcare systems, e-skins, and wearable applications.
Keywords: Amorphous gallium oxide; Atomic-layer deposition; Deep ultraviolet; Deep-ultraviolet wavelength; Flexible photodetectors; Gallium oxides; High flexibility; Ultra-violet photodetectors; Ultraviolet wavelength; Wide band-gap material; Amorphous gallium oxide; Atomic layer deposition; Deep-ultraviolet wavelengths; Flexible photodetectors; Wide-bandgap materials